What the Australian Public Knows About the High Court. (March 2019) - Nielsen, Ingrid; Smyth, Russell
Existing studies for the United States examine the extent to which the public is knowledgeable about US courts, arguing that knowledge of the courts is linked to public support for their role. We know little, though, about the Australian public's awareness of the High Court of Australia. We report the results of a survey of a representative sample of the Australian adult population, administered in November 2017. We find that few Australians know the names of the Justices, the number of Justices on the Court, how the Justices are appointed or for how long they serve. Awareness of recent cases decided by the Court is mixed. We find that age and education are better predictors of awareness levels than is gender. Our findings are important because in the absence of awareness of the High Court, the potential exists for the public to see the Court as having a more overt political role than it has, which may lower esteem for the Court. The potential for this to occur is exacerbated if, and when, politicians attempt to drag the High Court into the political fray, by attributing political motives to it that it does not have.